2020
DOI: 10.15280/jlm.2020.10.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Effects of Acute High-Intensity Resistance Exercise on Episodic Memory Function: Consideration for Post-Exercise Recovery Period

Abstract: Background: The present experiments evaluated the effects of acute high-intensity resistance exercise on episodic memory. Methods: Two experiments were conducted. For Experiment 1, participants (N = 40; Mage = 21.0 years) were randomized into one of two groups, including an experimental exercise group and a control group (seated for 20 min). The experimental group engaged in an acute bout of resistance exercises (circuit style exercises) for 15 minutes, followed by a 5-min recovery period. Memory function was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 73 publications
0
17
1
Order By: Relevance
“…As demonstrated thoroughly elsewhere [7], the post-exercise recovery period may play a key role in modulating the acute effects of exercise on memory function. Recent work from Loprinzi et al [39] suggests that a short (e.g., 5-min) recovery period with high-intensity resistance exercise may compromise performance on wordlist episodic memory task, but a longer duration recovery period (e.g., 10-20 min) after a single bout of high-intensity resistance exercise may improve word-list episodic memory. In contrast to these findings, Crush et al [7] suggests that a 5 min resting period with acute moderate-intensity treadmill exercise may have a favorable effect on memory functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated thoroughly elsewhere [7], the post-exercise recovery period may play a key role in modulating the acute effects of exercise on memory function. Recent work from Loprinzi et al [39] suggests that a short (e.g., 5-min) recovery period with high-intensity resistance exercise may compromise performance on wordlist episodic memory task, but a longer duration recovery period (e.g., 10-20 min) after a single bout of high-intensity resistance exercise may improve word-list episodic memory. In contrast to these findings, Crush et al [7] suggests that a 5 min resting period with acute moderate-intensity treadmill exercise may have a favorable effect on memory functioning.…”
Section: Discussionmentioning
confidence: 99%
“…2. Among these six studies, 16 standardized regression coefficient ESs were calculated: Loprinzi et al [39] produced six ESs (three each for exercise and non-exercise control groups) and the five other studies [1,19,25,29,51] each produced two ESs (one for exercise and another for non-exercise control groups). As illustrated by Fig.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Each circuit involved: For the last circuit (rest [laying] for 60 s), instead of a rest period, participants performed push-ups to failure for 1 min (with the option of performing knee push-ups, if needed). This acute resistance exercise protocol has been utilised in other related experiments (Loprinzi, Green, et al, 2020). After the bout of exercise, participants rested in a seated position for 10 min.…”
Section: Exercise Protocolsmentioning
confidence: 99%
“…These eight studies demonstrated mixed findings, underscoring the importance of conducting additional research on this topic, particularly acute resistance exercise studies. In a recent experiment, Loprinzi, Green, et al (2020) examined the effects of acute resistance exercise on episodic memory and demonstrated evidence of a potential spatial-and non-spatial memory enhancement effect, particularly if the post-exercise recovery period was of at least 10 min. This aligns with the meta-analysis by Chang et al (2012) showing greater effect sizes regarding the effects of acute exercise on cognitive function (globally) with post-exercise rest periods greater than 10 min (but less than 20 min).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acute aerobic exercise, emerging research also demonstrates that acute resistance exercise may influence memory. Using a circuit-style acute resistance exercise paradigm, Loprinzi et al [27] had participants complete five sets of exercises (e.g., push-ups, sit-ups, plank), with each set lasting 3-min, interspersed with a 1-min recovery between sets; the last set was completed to failure. Their results demonstrated that, among a young adult population, 15-min of acute resistance exercise was effective in enhancing episodic memory, specifically the "where" component of a spatial-temporal episodic memory task.…”
Section: Acute Exercise Modality On Memorymentioning
confidence: 99%